Strategi pembelajaran bahasa arab materi qira’ah di SMP Negeri 2 Kertanegara - Rahmawati, Tari; Yuslam, Yuslam (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: Learning strategy is a series of activities in the learning process related to student management, teacher management, management of learning activities, management of learning resources and assessment, so that learning activities can be carried out in accordance with the learning objectives set. Findings: This study aims to describe the strategy of learning Arabic material qira‟ah in SMP Negeri 2 Kertanegara, Purbalingga Regency. Methods: This research is a flied research that is descriptive qualitative in nature. Data obtained through interviews, observation, and documentation during the research. Technical data analysis, data reduction, presentation, data validity and conclusions. Conclusion: The results of the study show that in the qira‟ah material arabic learning strategy at SMP Negeri 2 Kertanegara as follows: the planning stage, the school holds a meeting first regarding learning Arabic to then get the result of the meeting with the planning steps, namely first, determining the allocation of time and effective weeks, then second namely compling an annual program, third compling a semester program, fourth making a learning syllabus and the last step in the planning process is compiling a lesson plan. At the learning strategy stage the strategy used in the qira‟ah strategy. At the implementation stage the qira‟ah learning strategy is systematic starting from the preminary activites carried out before the teacher explains the material then the core activities where the teacher explains the material then evaluation and closing.